Propuesta de diseño de una ruta turística de los Atractivos naturales de la parroquia Galeras, cantón Muisne, provincia de Esmeraldas - Moreno Hoyos, Karina Micaela (2021)
This research project was developed in Galera parroquia, in Muisne canton of Esmeraldas province. The general objective is the design of the tourist route of the natural attractions of this parroquia, to promote internal tourism that links the different existing related initiatives and improve the income. This research project was done using different methods and types of research. To identify the natural attractions, the cards provided by the Ministry of Tourism for the survey and hierarchization of the tourist attractions and collecting information through the field visit. The survey was used as a tool to determine the viability of the project, indicating that 72.6% of the citizens surveyed do not know this parroquia, and 61.3% are interested in getting to know it through a tourist route. The current natural attractions and the results of pleasures and preferences of the potential tourists obtained from the surveys was considered for design the tourist route map called “Cachalote”, in addition is created the logo and established the activities, tourist services and prices to be carried out in each place of the itinerary. Key words: Tourist route, natural attractions, itinerary, tourist potential